Moisture-induced autonomous surface potential oscillations for energy harvesting - Yu Long (Nature Portfolio, 2021)
Moisture-induced energy generation is a potential green energy power source. Here, the authors report a moisture-induced autonomous surface potential oscillation phenomenon and apply it to the demonstration of energy harvesters with long persistence time and good energy density